TEACHING INDONESIAN SONGS' MELODY IN TEACHING ESL/EFL CLASSROOM - Jannes Freddy Pardede (Universitas Negeri Padang, 2015)
Young leamers sometimes get bored even frustrated to learn English. There are many reasons why they feel like this. One of them is an inappropriate method of teaching. Psychologically, children usually like to play, relax, and have fun. They tend to be so dynamic and easily change their ccncentration from one to another. This situation also occurs in learning English. Therefore, teachers of English should be more creative in creating and applying various kinds of games, songs and any other activities. In this paper, the writer would like to show the influence of Indonesian songs' melody in learning English for young learners. Based on the writer's experience, teaching English songs is an effective way in attracting young leamer's concentration in learning English. In teaching, the writer translates some Indonesian songs' lyrics such as Bangun Tidur and Burung Kakak tua into English lyrics first. Through this way, learners can more focus on English words without getting difficulties in learning melody or rhythm of the scngs anymore because most of them have already been familiar with the songs in Indonesian version. The followings are some benefits of teaching English songs for young learners: l). Young learners become more active and enjoyful in learning English, 2) they can learn vocabulary with fun, 3) they can pronounce rvords nearly look like native speakers, 4) they can learn grammatical forms unconsciously, and 5) they can be more alert on spelling and corrected sounds.